2008
DOI: 10.1159/000123617
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Venous Flow Measurement May Predict the Clinical Behavior of a Fetal Extralobar Pulmonary Sequestration

Abstract: Objective: Fetal extralobar pulmonary sequestration (EPS) is sometimes complicated by a massive pleural effusion, leading to tension hydrothorax and fetal hydrops. The goal of this study was to examine sonographic signs of venous obstruction in fetal EPS with or without pleural effusion. Methods: Records of fetal ultrasound from 6 patients with EPS were reviewed with special attention to aberrant arterial and venous flow. The results were correlated with their clinical outcomes. Results: Four of the 6 cases (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…This arterial blood supply typically originates from the descending aorta or, rarely, from intercostal, gastric, or splenic arteries. Venous drainage can be systemic or pulmonary [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This arterial blood supply typically originates from the descending aorta or, rarely, from intercostal, gastric, or splenic arteries. Venous drainage can be systemic or pulmonary [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [9] found that BPS fetuses with a CVR >1.6 were prone to have fetal hydrops. Kitano et al [7, 8] found that obstruction of the drainage vein, manifested as a decrease in blood flow assessed by Doppler ultrasound, was associated with massive pleural effusion, though a large sample size is required to confirm their findings. Our study, which recruited a larger FBS cohort, showed that BPSs with SVD were more frequently complicated by hydrops and polyhydramnios than those with PVD, although the CVRs of the two groups did not differ from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis of the majority of cases is favorable, there are still some cases that develop hydrops and pulmonary hypoplasia, which can result in high intrauterine and neonatal mortality [3-6]. However, few factors have so far been found to correlate with different prenatal course and outcomes [7-9]. Kitano et al [7] were the first to apply assessment of the venous blood flow in BPS to predict clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P Velásquez Trujillo, et al 2016; 11 (supl): 78-81 una arteria sistémica separada, suministro arterial originado típicamente a partir de la aorta descendente y ocasionalmente desde la intercostal, celíaca o arterias esplénicas, mientras que el drenaje venoso es a través de las venas ácigos o la vena cava inferior y venas pulmonares 1 . Aunque 70% tienen regresión espontánea in-utero, puede progresar en el período intrauterino y solo unos pocos casos se asocian con un rápido crecimiento y/o derrame pleural e hidrops fetal (mortalidad entre 90% y 100%) 2 , secundarios a torsión de la masa con alteración u obstrucción del sistema linfático o venoso, volviéndose insuficiente, requiriendo tratamiento intrauterino, caracterizado por oclusión arterial mínimamente invasiva, a partir de cirugía fetal con toracotomía y secuestrectomía 3 , ablación arterial por fotocoagulación o inyección de sustancias esclerosantes o ablación por radiofrecuencia, convirtiéndose en tratamiento definitivo siendo innecesaria la resección postnatal 4 .…”
Section: Introductionunclassified